Professional standards as a factor for adapting human resources to industry 4.0: approaches for development and implementation in public administration - Araújo, Brenda de Jesus Moraes; Souza Júnior, Armando (Brazilian Journal of Production Engineering, 2023)
The progressive advances experienced in the production chain throughout history have placed us before the 4th Industrial Revolution, also known as Industry 4.0 (I4.0), marked by the extensive use of the Internet, robotics and digitization. There is a great perspective that governments promote I4.0 technologies in order to improve the management of public resources, as well as to allow overcoming the limitations of processes and state bureaucratic structures. However, the technological transformations introduced by this concept fundamentally change the working conditions of organizations and bring serious implications for jobs and professions. In this sense, the objective of the present study is to investigate the essential skills and abilities of the workforce for the implementation of I4.0 in the public sector. For this, a literature review was carried out in the Google Scholar (GA), Web of Science (WoS) and Scopus database. Content analysis showed that, in addition to the need for technical knowledge, it is imperative that workers have the ability to work under pressure, coordinate and solve complex problems, in addition to personal responsibility in decision-making. In the end, it was possible to derive a synthesized table, which identifies the dimensions that should be considered when evaluating professional standards for adaptation to I4.0.
Keywords: Industry 4.0; Skills; Human Resources; Public service